2019
DOI: 10.1051/0004-6361/201935062
|View full text |Cite
|
Sign up to set email alerts
|

Obscured AGN at 1.5 <z< 3.0 from the zCOSMOS-deep Survey

Abstract: Context. The physics and demographics of high-redshift obscured active galactic nuclei (AGN) is still scarcely investigated. New samples of such objects, selected with different techniques, can provide useful insights into their physical properties. Aims. With the goal to determine the properties of the gas in the emitting region of type 2 AGN, in particular, the gas metal content, we exploit predictions from photoionization models, including new parameterizations for the distance of gas distribution from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 104 publications
(138 reference statements)
0
52
0
Order By: Relevance
“…0, 8.40, 8,56, 8.69, 8.86, 9.00, respectively, Metallicity values in this range has been found for AGNs with redshifts varying from ∼ 0 to ∼ 7 (e.g. Nagao et al 2006a;Feltre, Charlot & Gutkin 2016;Matsuoka et al 2018;Thomas et al 2019;Mignoli et al 2019;Pérez-Montero et al 2019;Dors et al 2014Dors et al , 2015Dors et al , 2018. We found that photoionization models assuming (Z/Z⊙) > 2.0 produce similar intensities of N 2, therefore, only (Z/Z⊙) < = 2.0 were assumed in our analysis.…”
Section: Photoionization Modelsmentioning
confidence: 87%
“…0, 8.40, 8,56, 8.69, 8.86, 9.00, respectively, Metallicity values in this range has been found for AGNs with redshifts varying from ∼ 0 to ∼ 7 (e.g. Nagao et al 2006a;Feltre, Charlot & Gutkin 2016;Matsuoka et al 2018;Thomas et al 2019;Mignoli et al 2019;Pérez-Montero et al 2019;Dors et al 2014Dors et al , 2015Dors et al , 2018. We found that photoionization models assuming (Z/Z⊙) > 2.0 produce similar intensities of N 2, therefore, only (Z/Z⊙) < = 2.0 were assumed in our analysis.…”
Section: Photoionization Modelsmentioning
confidence: 87%
“…Storchi-Bergmann et al 1998;Feltre et al 2016;Castro et al 2017) and at high redshifts (e.g. Dors et al 2018;Mignoli et al 2019;Guo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, by imposing the same scaling relations at higher redshift, we computed a forward evolution of the galaxies at lower redshifts and towardsthe present time. In this framework, we also study the evolution of the galaxies that at redshift z = 2.2 follow the flat MZR as derived by Mignoli et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…We also analyze the temporal evolution and the fate of the galaxies with stellar masses, metallicities, and SFRs constrained by the high-redshift MZRs and MSRs. In particular, we discuss the implications of the newly observed flat MZR at redshift z = 2.2 by Mignoli et al (2019), who analyzed the metal content of 88 C iv-selected galaxies containing type 2 AGN with reliable measurements at high redshift.…”
Section: Introductionmentioning
confidence: 99%